Increasing Artistic Creativity for Children Aged 5–6 Years Through Pop-Up Book Media - Pasaribu, Nurul Azmi; Sit, Masganti (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study aims to improve the artistic creativity of children aged 5–6 years through pop-up book media at RA Islamiyyah Gunung Melayu. The method used was Classroom Action Research (CAR) employing the Kemmis and McTaggart model in two cycles. The research subjects were 23 children, consisting of 9 girls and 14 boys. Data were collected through observation and documentation, focusing on trying new ideas, involving others, and overcoming challenges. The results showed a significant increase: in the pre-cycle, only 25.5% of children were in the developing category, which increased to 75% in Cycle I and reached 93.75% in Cycle II in the very well-developed category. These findings indicate that pop-up book media is effective in stimulating children’s artistic creativity through enjoyable and interactive learning experiences.